2016
DOI: 10.14202/vetworld.2016.535-539
|View full text |Cite
|
Sign up to set email alerts
|

The structural and functional recovery of pancreatic β-cells in type 1 diabetes mellitus induced mesenchymal stem cell-conditioned medium

Abstract: Aim:Various studies have shown that secreted factors alone in culture medium without stem cell are capable of repairing tissues by itself in various conditions involving damaged tissue/organ. Therefore, this study was aimed to investigate the role of human umbilical cord mesenchymal stem cell-derived conditioned medium (CM) on the recovery of pancreatic β-cells in Wistar rats (Rattus norvegicus) with type 1 diabetes mellitus.Materials and Methods:The 0.05 ml CM induction was applied to the diabetic group of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…melatonin participation in pancreatic regeneration was attributed to its ability to scavenge free radicals as an antioxidant by stimulating messenger ribonucleic acid (mRNA) levels and activities of SOD and GPx (Maisaa and AL-Rawi, 2007;Vijayanand and Wesely, 2011;Tams, 2014and Godam et al, 2014 The present results indicated noticeable improvement of the pancreatic tissues after treatment of diabetic group with mescenchymal stem cells. These results are in agreement with Nugroho et al (2016) who reported that the structure of pancreatic tissues recovered in one week after MSCs treatment. Recent results obtained by Sato et al (2016) indicated that the sections from the pancreas after treatment with MSCs on day 28, showed apparently normal structure of both the pancreatic acini and the islets of Langerhans with their rounded and vesicular nuclei, such results confirm the present reported findings.…”
Section: Bhansali Et Al (2013)supporting
confidence: 93%
“…melatonin participation in pancreatic regeneration was attributed to its ability to scavenge free radicals as an antioxidant by stimulating messenger ribonucleic acid (mRNA) levels and activities of SOD and GPx (Maisaa and AL-Rawi, 2007;Vijayanand and Wesely, 2011;Tams, 2014and Godam et al, 2014 The present results indicated noticeable improvement of the pancreatic tissues after treatment of diabetic group with mescenchymal stem cells. These results are in agreement with Nugroho et al (2016) who reported that the structure of pancreatic tissues recovered in one week after MSCs treatment. Recent results obtained by Sato et al (2016) indicated that the sections from the pancreas after treatment with MSCs on day 28, showed apparently normal structure of both the pancreatic acini and the islets of Langerhans with their rounded and vesicular nuclei, such results confirm the present reported findings.…”
Section: Bhansali Et Al (2013)supporting
confidence: 93%
“…The secretome contained growth factors and interleukins that influenced intrapancreatic regeneration by activating and recruiting circulating stem cells and progenitor cells to injured sites, where they collaborate to repair damaged tissue. Additionally, previous research has demonstrated that MSCs circulate in injured locations and develop specifically inside tissue [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the administration of MSC-CM to bone fracture cases gives good results as indicated by the accelerated regeneration of the bone. The extracts of MSCs growth media used in this study have also been reported to give good results on the regeneration of skin burns [ 30 ], skin wound [ 31 ], and beta cells of the pancreas in rats with type 1 diabetes mellitus [ 32 ].…”
Section: Discussionmentioning
confidence: 99%